2022
DOI: 10.1136/bmjopen-2021-058326
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the diversity of consumers engaged in guidelines: a scoping review

Abstract: BackgroundGuideline developers are encouraged to engage patients, carers and their representatives (‘consumers’) from diverse backgrounds in guideline development to produce more widely applicable guidelines. However, consumers from diverse backgrounds are infrequently included in guidelines and there is scant research to support guideline developers to do this.ObjectivesTo identify principles and approaches to broaden the diversity of consumers engaged in guideline development.DesignScoping review and semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
3
0
3
Order By: Relevance
“…⇒ Findings from some of the included studies indicate that online discussions and crowdsourcing campaigns may be cost-effective and efficient ways to engage relevant stakeholders in decision-making processes, but that decision-makers should also be engaged in these processes in order to ensure real influence. 35 integrating citizen engagement into evidence-informed health policymaking, 36 citizen juries in health policymaking, 37 online citizen participation in deliberation and policymaking, [38][39][40] deliberative mini-publics, 41 42 approaches to broaden the diversity of consumers engaged in guideline development, 43 the effect of municipality size on political efficacy and participation, and evaluation tools for patient and public engagement in research and health system decision-making. 44 The aim of this review is to inform decisions about how best to implement and/or facilitate public participation in deliberations and decisions about infection prevention and control measures.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…⇒ Findings from some of the included studies indicate that online discussions and crowdsourcing campaigns may be cost-effective and efficient ways to engage relevant stakeholders in decision-making processes, but that decision-makers should also be engaged in these processes in order to ensure real influence. 35 integrating citizen engagement into evidence-informed health policymaking, 36 citizen juries in health policymaking, 37 online citizen participation in deliberation and policymaking, [38][39][40] deliberative mini-publics, 41 42 approaches to broaden the diversity of consumers engaged in guideline development, 43 the effect of municipality size on political efficacy and participation, and evaluation tools for patient and public engagement in research and health system decision-making. 44 The aim of this review is to inform decisions about how best to implement and/or facilitate public participation in deliberations and decisions about infection prevention and control measures.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Systematic reviews with a broader focus have found limited evidence of the effects of public involvement in healthcare planning and policy. 20 30–34 Other systematic reviews have explored multi-stakeholder activities to control COVID-19, 35 integrating citizen engagement into evidence-informed health policymaking, 36 citizen juries in health policymaking, 37 online citizen participation in deliberation and policymaking, 38–40 deliberative mini-publics, 41 42 approaches to broaden the diversity of consumers engaged in guideline development, 43 the effect of municipality size on political efficacy and participation, and evaluation tools for patient and public engagement in research and health system decision-making. 44 …”
Section: Introductionmentioning
confidence: 99%
“…Sowohl der partizipative als auch der Konsultationsansatz haben Vorteile und Herausforderungen. Sie können kombiniert werden, um ein breitgefächertes Meinungsbild zu erreichen und die Repräsentanz der Betroffenenperspektive und die der Angehörigen zu erhöhen [5,20,25].…”
Section: Die üBerwindung Von Diskrepanzen Zwischen Wissenschaftlicher...unclassified
“…Dies deckt sich mit dem Forschungsstand [9,11,12,15] für LL allgemein. Ideal wäre eine Partizipation über alle Phasen des LLE mit Stimmrecht [19,20]. Die AWMF empfiehlt die Einbeziehung der Betroffenenperspektive in die LLE, formuliert dies aber nicht als Verpflichtung [4].…”
Section: Datenanalyseunclassified
“…Zur Bewertung der Qualität der Patient*innenbeteiligung entwickelten sie einen Monitoring-und Evaluationsrahmen, der sowohl Prozessals auch Ergebniskriterien umfasste (Berücksichtigung des Inputs der Patient*innen im LL-Text, unterstützende Haltung von Fachleuten, Beachtung der Patient*innenbeteiligung, Beteiligung eines Team-Monitors). Darüber hinaus empfehlen Synnot et al [39] in ihrem scoping Review kreative und situationsangepasste Methoden zur Einbindung diverser Gruppen und zum Aufbau langfristiger Ver-trauensbeziehungen, in denen auch vorbelastete Menschen wissen, dass sie gehört und respektiert werden.…”
Section: Australienunclassified